Forbidden lust - Booth, Karen (Karen B.) (Booth, Karen (Karen B.). Dynasties: seven sins., 2020)
A secluded island resort is the perfect romantic setting for the night of passionate abandon Allison Randall plans to share with Zane Patterson. Her elder brother's best friend has always been off-limits ... and Zane is determined to keep it that way. But when a storm strands them together, neither can hold back. Everything Allison dreamed of is finally in reach ... until unwelcome revelations threaten a rude awakening!